Geographic variation in killer whale colour patterns - Mäkeläinen, Pirjo (Helsingin yliopisto, 2020)
The killer whale (Orcinus orca) is an elegantly patterned top predator, which is the largest species in the dolphin family. Great climatic changes and oscillations in weather conditions in the past have influenced many dolphin species. They have needed to adapt and disperse to new and changing environments. Diversification of the species has led to polymorphism and made the taxonomy of many dolphin species challenging. There are also great differences and specialization within the killer whale species, but no subspecies have been accepted yet. I have focused on variation in colour patterns and coloration in populations around the world, mainly in saddle patch and eye patch patterns. We have showed that killer whale eye patch shapes remain constant over time and that they are a great additional tool for identification. Eye patch size and orientation can also be population specific. I also studied the symmetry of the coloration and possible effects causing fluctuating asymmetry in killer whales saddle patch pattern in North Pacific Ocean populations. When normally symmetrical features develop asymmetrically in nature, there is often some environmental or genetic stress causing it. Some individuals with good fitness can resist that stress, but those who cannot resist it may show causing asymmetry in normally symmetrical features. The southern resident population had much more fluctuating asymmetry in their saddle patch pattern than the other populations. Although transient killer whales are the most contaminated of the populations they were still quite symmetrical. Low genetic variability and small population size may be the reasons for southern resident asymmetries. North Atlantic killer whale populations are somewhat specialized, but there were not great differences in their saddle patch pattern. It may be due to their recent diversification. A group of killer whales were observed off the west coast of Scotland, that all had slanting eye patches. These eye patches differed from other North Atlantic eye patches as ...